2013
DOI: 10.1364/oe.21.013626
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency self-induced oscillations in a silicon nanocavity

Abstract: We show that self-induced oscillations at frequencies above GHz and with a high spectral purity can be obtained in a silicon photonic crystal nanocavity under optical pumping. This self-pulsing results from the interplay between the nonlinear response of the cavity and the photon cavity lifetime. We provide a model to analyze the mechanisms governing the onset of self-pulsing, the amplitudes of both fundamental and harmonic oscillations and their dependences versus input power and oscillation frequency. Theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 31 publications
(52 reference statements)
4
20
0
2
Order By: Relevance
“…Similar dynamics was found in other passive devices, ranging from Fabry-Perot resonators (Ogusu et al 1998) and distributed feedback structures (Winful and Cooperman 1982;Parini et al 2007) to microring (Priem et al 2005;Van Vaerenbergh et al 2012a;Chen et al 2012;Kusko 2013) and microdisk (Abrams et al 2014) resonators and nanocavities in photonic crystals (Cazier et al 2013;Yang et al 2014). Most of the recent works deal with silicon cavities where thermal and free-carrier effects have to be considered (Priem et al 2005;Van Vaerenbergh et al 2012a, b;Chen et al 2012;Abrams et al 2014;Cazier et al 2013;Yang et al 2014;Malaguti et al 2011;Zhang et al 2013).…”
Section: Introductionsupporting
confidence: 70%
“…Similar dynamics was found in other passive devices, ranging from Fabry-Perot resonators (Ogusu et al 1998) and distributed feedback structures (Winful and Cooperman 1982;Parini et al 2007) to microring (Priem et al 2005;Van Vaerenbergh et al 2012a;Chen et al 2012;Kusko 2013) and microdisk (Abrams et al 2014) resonators and nanocavities in photonic crystals (Cazier et al 2013;Yang et al 2014). Most of the recent works deal with silicon cavities where thermal and free-carrier effects have to be considered (Priem et al 2005;Van Vaerenbergh et al 2012a, b;Chen et al 2012;Abrams et al 2014;Cazier et al 2013;Yang et al 2014;Malaguti et al 2011;Zhang et al 2013).…”
Section: Introductionsupporting
confidence: 70%
“…[16][17][18][19] Studies have shown abundant nonlinear behaviors promoted by the highly localized optical field inside the microcavities, such as optical bi-stability, 20,21 deformation and abnormal oscillation [22][23][24][25][26][27] of the transmission spectra. Recently, periodic self-sustained pulsation (SSP) [28][29][30][31][32] in the transmission spectrum has been reported in various microcavity systems, excited by a fixed-frequency continuous laser, different from that excited by frequency-scanned lasers 26 or by pulsed lasers 27 in previous studies. For instance, very fast SSPs at the GHz level have been reported in silicon microcavities 28,29 resulting from coupled electron-photon dynamics.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, periodic self-sustained pulsation (SSP) [28][29][30][31][32] in the transmission spectrum has been reported in various microcavity systems, excited by a fixed-frequency continuous laser, different from that excited by frequency-scanned lasers 26 or by pulsed lasers 27 in previous studies. For instance, very fast SSPs at the GHz level have been reported in silicon microcavities 28,29 resulting from coupled electron-photon dynamics. Moreover, in silica microcavities or silica/polymer hybrid microcavities where there are no free carriers, SSPs have also been observed, formed by the interplay between thermo-optic effect and Kerr effect, 30 or between thermo-optic effect and mechanical motion.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The quality factor of the cavities that we studied is in the range Q = 1000−3000, corresponding to a cavity lifetime of the same order as the fast diffusion time (about 3 ps, [5]) of the free carriers. Note that cavities with ultra-high quality factor, working at lower speed, can experience also other phenomena like for example regenerative oscillations [32][33][34] or self-pulsing [35], but they happen on a much longer time scale than the effects investigated here.…”
mentioning
confidence: 79%